2006
DOI: 10.1002/adma.200600997
|View full text |Cite
|
Sign up to set email alerts
|

(Fe,Mn)3O4 Nanochannels Fabricated by AFM Local‐Oxidation Nanolithography using Mo/Poly(methyl methacrylate) Nanomasks

Abstract: Epitaxial (Fe,Mn)3O4 thin films are patterned into nanochannels using molybdenum/poly(methyl methacrylate) (PMMA) nanomasks realized by combining local anodic oxidation of Mo and dry etching of PMMA. Nanostructures on the 100 nm scale can be easily fabricated by subsequent wet chemical etching with H3PO4 (see figure). (Fe,Mn)3O4 nanochannels open the possibility of fabricating spin‐polarized nanocircuits for room‐temperature spintronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…[10][11][12] In the amplitude modulation ͑AM͒ mode 13 ͑AM-AFM͒, either the sample or the tip is scanned in a raster fashion while a feedback mechanism keeps the oscillation amplitude of the cantilever-tip system a fixed value ͑set-point amplitude͒. The variations in the z-scanner position are reported as topographic images while the variations in the phase shift between the external excitation and the cantilever response provide a compositional map of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In the amplitude modulation ͑AM͒ mode 13 ͑AM-AFM͒, either the sample or the tip is scanned in a raster fashion while a feedback mechanism keeps the oscillation amplitude of the cantilever-tip system a fixed value ͑set-point amplitude͒. The variations in the z-scanner position are reported as topographic images while the variations in the phase shift between the external excitation and the cantilever response provide a compositional map of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Rolandi et al first reported AFM lithography using Mo and Mo/poly͑methyl methacryate͒͑PMMA͒ nanomasks for the patterning of structures on Si and SiO 2 , 11 and we have successfully expanded the scope of this technique to the nanofabrication of transition metal oxides. 12 This Mo/PMMA technique enables us to fabricate various kinds of nanostructures even in insulating materials in principle. In this technique, the mask includes an organic PMMA layer, which brings a complicated procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, templates to build molecular architectures, 6,7 resist masks, 8 nanomechanical resonators, 9,10 or several nanoelectronic devices and transistors [11][12][13][14] have been fabricated by local oxidation. In AFM oxidation, the tip is used as a cathode and the water meniscus formed between the tip and the surface is the source of the oxyanions species.…”
mentioning
confidence: 99%